Anatomical variation of circle of Willis in computed tomographic angiography study - Barakoti, Abiral; Regmi, Shubhekshya; Khadka, Hensan (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: The circle of Willis (CW) is located at the base of the brain, connecting the carotid and vertebral-basilar arterial systems. Cerebral computed tomographic angiography (CTA) has high sensitivity and specificity in detecting intracranial vascular variations. The aim of this study was to identify anatomic variations in the CW using cerebral CTA and to compare these variations based on age and gender.Methods: A cross-sectional study was conducted among total of 54 patients referred for CTA who met the inclusion criteria were evaluated. Data on age, gender, and the presence of anatomical variations in the CW were collected and analyzed using SPSS version 26.0.Results: The study included 54 participants, with a male-to-female ratio of 1.45:1 and ages ranging from 3 to 87 years. The most common anatomical configuration was Type A anterior CW (75.9%), followed by hypoplasia of the bilateral posterior communicating arteries / Type E posterior CW (38.9%). Complete anterior and posterior circulation was observed in 16.6% of participants, and the proportions of complete CW configuration were similar in males and females (p = 0.501 and 0.391 for anterior and posterior CW, respectively) as well as in younger (under forty) and adult (forty or older) participants (p=1 for both anterior and posterior CW), without statistically significant differences. Fetal PCA was observed in 24.1% of participants, with the unilateral type being more common (61.5%), and there was no correlation with the participants' gender.Conclusions: This study identified common anatomical variations in the Circle of Willis using cerebral CTA. Type A anterior CW and Type E posterior CW were most prevalent, with no significant differences in completeness based on gender or age. Fetal PCA was observed in 24.1% of participants, primarily in the unilateral form, without gender correlation. These findings highlight the importance of recognizing anatomical variations in the Circle of Willis for improved clinical decision-making and diagnostic accuracy in neurovascular assessments.